Mediating Role of Green Supply Chain Management Between Lean Manufacturing Practices and Sustainable Performance - Awan, Fazal Hussain; Dunnan, Liu; Jamil, Khalid; Mustafa, Sohaib; Atif, Muhammad; Gul, Rana Faizan; Guangyu, Qin (Frontiers in Psychology, 2022)
Manufacturing companies in today's industrial world are seeking to use the new manufacturing process methods. The primary goal of corporations is to achieve optimum production by deploying minimal capital. The fundamental purpose of this study is to examine the influence of various lean manufacturing practices on the company's sustainability performance and the mediating role of green supply chain management (GSCM). The data was gathered using questionnaires from two hundred and fifty Pakistani manufacturing firms and analyzed using AMOS 25. Results demonstrate that process and equipment, product design, supplier relationships, and customer relationships significantly affect sustainable performance. It is also recognized that Green Supply Chain Management mediates the interaction between HR processes, product design, supplier relationship, customer relationship and environmental performance. This study's findings will enable managers and decision-makers of manufacturing companies to increase sustainable efficiency and reduce waste through the use of lean manufacturing and GSCM implementation.